Building Community Cohesion for Effective Community Participation in Community-Based Tourism - Rop, Judy Jepchirchir; Manono, George; Kiptanui, Rotich D. (International Journal of Tourism & Hospitality Reviews, 2023)
Purpose: The purpose of this research was to determine the influence community cohesion has in enabling effective Community participation in community-based tourism within Kisite Mpunguti Ecosystem. Methodology: Adopting descriptive and explanatory research design, the study employed both quantitative and qualitative methods in data collection; community households within Kisite Mpunguti Ecosystem are involved in community-based tourism for semi-structured questionnaires. Quantitative data was processed using descriptive and inferential statistics with content analysis used for qualitative data. Main findings: Although community cohesion had a negative association with community participation, the relationship to community participation was significant thus concluding it as a determinant in enabling successful community participation in community-based tourism through elements like inclusion, belonging, equality, recognition, and trust among others. Applications: This study is useful in the field of Rural and Community Based tourism on the element of factors enabling community participation in tourism, in this case, the community cohesion factor, especially in rural areas with unutilized tourism resources and the need for alternative sources of income. Novelty: Findings provide knowledge to existing Community Based Tourism Projects nationwide on the vital role played by community cohesion anchored on principles like trust, equity, transparency, sharing responsibilities, commitment, and respect for one another and authority in achieving effective participation.